Lung volumes 24 Hours after Laparoscopic Cholecystectomy — Justification for Early Discharge - Jameel Ali; Theophilus J Gana (Canadian Respiratory Journal)
OBJECTIVE: To compare lung volumes after laparoscopic cholecystectomy (LC) and open cholecystectomy (OC).